ETIKA BISNIS ISLAM DALAM PERSPEKTIF FIKIH MUAMALAH - Indah Rencani (CV. Adiba Aisha Amira, 2026)
Islamic business ethics refers to a set of moral principles derived from Islamic teachings that guide business conduct in accordance with Sharia law. From the perspective of fiqh muamalah, business activities are not solely profit-oriented but must also uphold justice, honesty, and social responsibility. This study aims to examine Islamic business ethics based on the principles of fiqh muamalah and its application in modern business practices. The research employs a qualitative approach through literature review.The findings indicate that Islamic business ethics emphasize key principles such as honesty (shiddiq), trustworthiness (amanah), justice ('adl), and social responsibility. Furthermore, Islam strictly prohibits business practices involving riba (usury), gharar (uncertainty), and maysir (gambling/speculation). The implementation of these ethical values is believed to contribute to a fair and sustainable economic system.